Effectiveness of sugammadex for cerebral ischemia/reperfusion injury - Sule Ozbilgin; Osman Yılmaz; Bekir Ugur Ergur; Volkan Hancı; Seda Ozbal; Serhan Yurtlu; Sakize Ferim Gunenc; Bahar Kuvaki; Burcu Ataseven Kucuk; Ali Rıza Sisman (Kaohsiung Journal of Medical Sciences, 2016)
Cerebral ischemia may cause permanent brain damage and behavioral dysfunction. The efficacy and mechanisms of pharmacological treatments administered immediately after cerebral damage are not fully known. Sugammadex is a licensed medication. As other cyclodextrins have not passed the necessary phase tests, trade preparations are not available, whereas sugammadex is frequently used in clinical anesthetic practice. Previous studies have not clearly described the effects of the cyclodextrin family on cerebral ischemia/reperfusion (I/R) damage. The aim of this study was to determine whether sugammadex had a neuroprotective effect against transient global cerebral ischemia. Animals were assigned to control, sham-operated, S 16 and S 100 groups. Transient global cerebral ischemia was induced by 10-minute occlusion of the bilateral common carotid artery, followed by 24-hour reperfusion. At the end of the experiment, neurological behavior scoring was performed on the rats, followed by evaluation of histomorphological and biochemical measurements. Sugammadex 16 mg/kg and 100 mg/kg improved neurological outcome, which was associated with reductions in both histological and neurological scores. The hippocampus TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) and caspase results in the S 16 and S 100 treatment groups were significantly lower than those of the I/R group. Neurological scores in the treated groups were significantly higher than those of the I/R group. The study showed that treatment with 16 mg/kg and 100 mg/kg sugammadex had a neuroprotective effect in a transient global cerebral I/R rat model. However, 100 mg/kg sugammadex was more neuroprotective in rats.